Grammar in use across time and space : deconstructing the Japanese 'dative subject' construction - Sadler, Misumi (Studies in discourse and grammar ;, 2007)
This monograph contains the first systematic investigation of the Japanese 'dative subject' construction across time and space. It demonstrates that, in order to capture what speakers/writers know about how to put an utterance or a clause together, it is necessary to pay attention to what they do in actual language use and in different discourse types. The work also shows the importance of diachronic perspectives to help us better understand the ways in which a particular grammatical structure is represented synchronically. By utilizing modern Japanese conversation, contemporary Japanese novel.